Perkembangan Perbankan Syariah pada Era Ekonomi Digital - Delima Delima; Muhammad Ikhsan Fadhillah (Asosiasi Riset Ilmu Manajemen dan Bisnis Indonesia, 2025)
Indonesian Islamic banking has undergone significant transformation in the digital era through the adoption of technologies such as mobile banking, digital wallets, P2P lending, robo-advisors, and blockchain. Digitalization improves service efficiency, reduces costs, and expands access to remote areas. However, challenges arise related to cybersecurity, low literacy and inclusion of Islamic finance, limited digital human resources, and regulations that are not yet in line with technological developments. Integrated efforts including education, strengthening security, human resource development, innovation of Islamic products, and collaboration with the halal ecosystem are needed to ensure sustainable growth of this sector.